Slovenščina na prvi pogled – poletna šola na Filozofski fakulteti Univerze v Mariboru - Ulčnik, Natalija; Nikolovski, Gjoko (Slavia Centralis, 2022)
From August 29 to September 10, 2022, the first summer school Slovenian at first Glance was held at the Department of Slavic Languages ​​and Literatures of the Faculty of Arts of the University of Maribor, intended for students who are learning Slovenian as a second and foreign language or would like to learn it or refresh and upgrade their knowledge.
Keywords: Slovenian at first Glance; summer school; Department of Slavic Languages ​​and Literatures; Slovenian as a second and foreign language; report